A Continuing narrative on Philippine theater the story of PETA (Philippine Educational Theater Association) - Samson, Laura L.; Velasco, Jovenal D.; Philippine Educational Theater Association (Quezon City Philippine Educational Theater Association, 2008)
"The Story of PETA may be considered a collective biography that provides a comprehensive yet intimate account of its lifework, from 1967- to 2007. It highlights the company?s unique approach and contribution to Philippine theater aesthetics, performance and pedagogy, and to popular education."--Back cover.
Part 1. 1967-1972 : envisioning a national theater -- A visionary's blueprint -- 1967 : the birthing of PETA -- 1967 : the PETA Kalinangan Ensemble : the beginnings of PETA's contemporary Philippine theater dramaturgy and aesthetics -- Central Institute for Theater Arts in the Philippines (CITAP) : from professional theater training to network organizing -- From the PETA national network to the International Theater Institute : from national linkage to global projection -- Taunting the Marcoses -- The founder's syndrome -- Part 2. 1973-1986 : building a people's theater -- Organizational biography, 1973-1986 : rebirth and transformation under authoritarian rule -- Kalinangan Ensemble : developing a theory and practice of people's theater aesthetics -- CITASA 1973-1986 : dynamic pedagogy and outreach -- Metropolitan Teen Theater League : the socially-oriented youth -- The national theater movement takes wing : Makiisa I (1983) and Makiisa II (1984) -- 1973-1986 in retrospect : thoughts after the haul -- Part 3. 1987-2007 : PETA comes of age and presences the future -- PETA's organizational journey -- PETA's foray into broadcast theater -- PETA's theater collectives and the emerging theater for development practice -- Metropolitan Teen Theater League : youth participation through theater education -- School of People's Theater and the PETA training and education program -- The Kalinangan Ensemble and the PETA performance program -- The Theater Center story -- Synthesis : the PETA person speaks -- Postscript.
Keywords: Philippine Educational Theater Association; Theaterical companies -- Philippines -- History; Theater -- Philippines -- History